Tolerance against brown planthopper (Nilaparvata lugens) in wild rice (Oryza sativa) accessions - SANDHU, RAJWINDER KAUR; SARAO, PREETINDER SINGH (The Indian Journal of Agricultural Sciences, 2022)
Brown planthopper, Nilaparvata lugens (StÃ¥l), is a major insect pest of rice in all the rice growing areas of the world. In the present study, the tolerance mechanism of resistance in wild rice accessions belonging to different Oryza species such as O. nivara (IRGC104646, CR100204), O. australiensis (IRGC105275, IRGC105270), O. punctata (IRGC99577) along with resistant check, Ptb33 and susceptible check, TN1 has been studied. The experiments were carried out on 30-days old plants under glasshouse conditions during kharif 2017 and 2018. IRGC99577 (22.80 and 24.00) took maximum days to hopper burn condition during both seasons. Functional plant loss index (%) was minimum in IRGC99577 (18.10%) followed by Ptb33 (20.96%) and IRGC104646 (29.47%). Least plant dry weight loss index (mg) was observed in Ptb33 and highest in TN1 during both the seasons. Overall, results indicated that rice accessions, IRGC99577 and IRGC104646 showed high levels of tolerance as compared to other wild rice accessions that were tested. The identified accessions thus could serve as potential sources of resistance in breeding BPH resistant varieties.